An Examination of Attempted Murder in Islamic Criminal Law - Bancin, Muhammad Al Amin; Suparmin, Sudirman (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
This research examines attempted murder (qatl al-amd) in Islamic criminal law, which is considered a serious offense with strict legal consequences. In Islamic law, the intention (niyyah) and concrete action to kill someone are seen as morally and legally equivalent to the successful act of murder, referring to the principles of protection of human life (hifz al-nafs) and justice (‘adl). Attempted murder can arise in a variety of situations, including physical attacks with weapons or other life-endangering devices. This research explores the main criteria in assessing attempted murder, namely the existence of an intention to kill as well as concrete actions to achieve that goal. Based on a normative juridical approach and analysis of primary legal texts, the study found that Islamic law provides for proportionate punishment while taking into account factors such as the intention of the perpetrator, the condition of the victim, and the social context of the event. In addition, the principle of reconciliation in Islamic law emphasizes the need